Race, Neighborhood Context, and Strategies to Avoid Victimization Among Female Probationers and Parolees. (October 2014) - Cobbina, Jennifer E.; Morash, Merry; Kashy, Deborah A.; Smith, Sandi W.
An established body of literature shows that females have higher levels of fear than males. Research suggests that women typically resort to rather constraining behavioral actions that limit their participation in public life. However, it is unclear whether the strategies women use to avoid victimization are tied to community context, especially for high-risk populations, such as women offenders. We build from insights of previous research by examining what strategies female probationers and parolees use to avoid victimization and their perception of how effective such strategies are in keeping them safe, whether the subjective and objective measures of neighborhood context is related to women's strategies and whether the strategies used to avoid victimization vary by race and economic status.